(untitled) (PANGEEA, 2026)
The study addresses the georeferencing process from an integrated perspective, examining the stages of acquisition, processing, and mathematical interpretation of spatial data. The control points used, defined virtually within the digital environment, function as coordinate-bearing elements that underpin the alignment of the raster image within a coherent projection system. The georeferencing procedure is analyzed both procedurally and mathematically, through the determination of transformation parameters and the evaluation of residual errors using the RMS indicator. The results emphasize the importance of correct data preprocessing and the relevance of mathematical interpretation in ensuring the geospatial accuracy of georeferenced imagery.